Influence of students' learning style and personality characteristics on their mathematics problem-solving skills - Sitorus, Jonni; Sinaga, Bornok; Handayani, Lili; Siagian, Dumora Jenny Margaretha (Frontiers in Education, 2025)
Problem-solving skills of students are indicators of their intellectual behavior, and they determine higher-order thinking skills that students need to master. One of the approaches to improving students' mathematics problem-solving skills is understanding their learning style and personality characteristics and the influences of these two factors on problem-solving skills. The research goals are to describe students' mathematics problem-solving skills and examine the influence of gender, grade level, learning style, personality characteristics, and interaction between learning style and personality characteristics on their mathematics problem-solving skills. The study population comprised all students in five state elementary schools and five state junior high schools, with a sample size of 200 students. Statistical analysis of the data was carried out using t-tests and analysis of variance. The majority of students showed “moderate” mathematics problem-solving skills (72.77), with 60.50% falling under the “moderate” category or above. Gender and grade level had a significant influence on students' mathematics problem-solving skills. In addition, mathematics problem-solving skills were dependent on learning style and personality characteristics. Learning style, personality characteristics, and interaction between these two factors showed significant influences on students' mathematics problem-solving skills. Furthermore, the learning style “auditory-kinesthetics” and the personality characteristics “steadiness-compliance” and “dominance-influence” had significant influences on students' mathematics problem-solving skills. Moreover, “auditory-kinesthetics—steadiness-compliance” and “auditory-kinesthetics—dominance-influence” interactions showed significant influences on students' mathematics problem-solving skills.